Exploring Students' Perceptions of ChatGPT in Higher Education: A Qualitative Study of Critical Thinking, Learning Autonomy, and Academic Ethics - Rani Servia; Sukri Adani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study explored students' perceptions of ChatGPT in higher education, focusing on its role in critical thinking development, learning autonomy, and academic ethics. Using a qualitative descriptive case study, data were collected from 15 eighth-semester English Education students at STKIP Muhammadiyah Aceh Barat Daya through semi-structured interviews and were analyzed using Braun and Clarke's thematic analysis with the support of NVivo 12. The findings revealed three main themes. First, students perceived that ChatGPT supported critical thinking by helping them analyze information, develop arguments, and verify AI-generated responses using reliable sources. Second, ChatGPT promoted learning autonomy by providing immediate access to information, supporting skill development, and encouraging self-directed learning. Third, students recognized the importance of using ChatGPT ethically by revising AI-generated content, avoiding plagiarism, and adhering to the principles of academic integrity. Overall, the findings suggested that ChatGPT was perceived as a valuable learning support tool when used critically, independently, and responsibly. The study highlighted the need for clear institutional guidelines to promote the ethical and effective use of generative AI in higher education.